In Situ Reaction Monitoring Reveals a Diastereoselective Ligand Exchange Reaction between the Intrinsically Chiral Au38(SR)24 and Chiral Thiols - Knoppe, Stefan; Azoulay, Raymond; Dass, Amala; Bürgi, Thomas (Journal of the American Chemical Society, 2012)
The ligand exchange reaction between racemic Au38(2-PET)24 (2-PET = 2-phenylethylthiolate) clusters and enantiopure 1,1′-binaphthyl-2,2′-dithiol (BINAS) was monitored in situ using a chiral high-performance liquid chromatography approach. In the first exchange step, a clear preference of R-BINAS for the left-handed enantiomer of Au38(2-PET)24 is observed (about 4 times faster than reaction with the right-handed enantiomer). The second exchange step is much slower than the first step. BINAS substitution deactivates the cluster for further exchange, which is attributed to (stereo)electronic effects. The results constitute the first example of a ligand exchange reaction in a thiolate-protected gold cluster with directed enrichment of a defined species in the product mixture. This may open new possibilities for the design of nanomaterials with tailored properties.